OVERCOMING DIFFICULTIES IN UNDERSTANDING SATIRE WHEN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Тюрина, Ю.С. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
Тhis article aims to reveal the main theoretical aspects of satire as a genre of literature and a popular humorous reception in the media and on television. It contains the concept of what constitutes satire, its classification and basic techniques, as well as the social and psychological functions of satire in literature and media.
Keywords: satire; irony; sarcasm; learning English as a foreign language; satirical literature; satire in the media